Adjustment to Chinese Culture and Mental Health Issues among Foreign Students on Chinese University Campuses during the COVID-19 Pandemic: A Collaborative Ethnographic Study - Jian Li; Eryong Xue; Yunshu He (Behavioral Sciences, 2023)
Foreign students in China may have difficulty adjusting to Chinese culture and may experience mental health problems related to acculturation, interpersonal issues, and social communication within the context of campus life. Therefore, this study attempts to apply a collaborative ethnography approach to explore the adjustment to Chinese culture and mental health issues among foreign students on Chinese campuses during the COVID-19 pandemic. We spent 16 months exploring the feelings and perceptions of 82 foreign international undergraduate students at six Chinese higher education institutions regarding their adjustment to Chinese culture and gathered their suggestions about how to address the mental health issues experienced by foreign learners in China. The results show that international students tend to have a limited understanding of Chinese culture and rely on very few channels for information—in particular, the Internet, teachers’ lectures, and daily life—which can easily result in mental health problems and thoughts of marginalization. In addition, the results showed that international students’ mental health problems are subjectively positively correlated with their own personality, cultural intelligence, and cultural identification ability and objectively related to their cultural distance and all aspects of the educational work of international students. It is suggested that Chinese higher education institutions should strengthen their attention to the mental health of international students in China and promote international students’ cross-cultural adaptation abilities and understanding of Chinese culture.